Aspek Perancangan Monitoring Antrian Kendaraan Pada Persimpangan Lampu Merah - Aeromidi Simanungkalit; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The number of vehicles in the big cities has increased rapidly, this phenomena has triggered an over density situation in the traffic light. The purpose of this study is to develop a tool to measurethe density of vehicles with sensors and RF 433Mhz as transmission media. To realize these tools, three ultrasonic sensors are used as a detector of the presence of a vehicle with a sensor with an object placed between 3 cm to 3 m and the distance between each sensor 50 m. The measurement values obtained from the measurement results shown through PLX-DAQ applications. In the design of this system is to perform testing of the tool, the measurement results can be analyzed todetermine the density of vehicles that can be categorized by the level of density, loose, short, medium and long. This paper has proposed a monitoring of traffic density in the traffic light.Keywords: RF Transceiver, PLX-DAQ, Ultrasonik Sensor, Traffic Density Information